(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article focuses on the fundamental role of mathematics in understanding and learning physics. The complex relationship between mathematics and physics has been the foundation of scientific discovery and technological progress for centuries. This synergy is evident in the formation, description, and interpretation of physical phenomena and laws, and information is given about the role of mathematics in the study of physics.